In Search of a Field-Based Relationship Between Benthic Macrofauna and Biogeochemistry in a Modern Brackish Coastal Sea - Gogina, Mayya; Lipka, Marko; Woelfel, Jana; Liu, Bo; Morys, Claudia; Böttcher, Michael E.; Zettler, Michael L. (Frontiers in Marine Science, 2018)
During several cruises in the southern Baltic Sea conducted in different seasons from 2014 to 2016, sediment cores were collected for the investigation of pore-water biogeochemistry and associated nutrient fluxes across the sediment-water interface. Six stations were positioned along a salinity gradient (ranging from 22 to 8) and covered various sedimentary habitats ranging from mud to sand. Integrated fluxes of nutrients in the supernatant water and sediment oxygen consumption were additionally derived from incubations of intact sediment cores. Subsequently, sediment from the pore-water and incubation cores was sieved for taxonomic identification and estimation of benthic macrofauna density. This combined dataset was used to determine the dominant factors influencing the vertical distribution of geochemical parameters in the pore-waters of the studied habitats and to find similarities and patterns explaining significant variations of solute fluxes across the sediment-water interface. A statistical relationship between the thickness of sulfide-free surface sediments, solute fluxes of sulfide, ammonium and phosphate as well as oxygen consumption and taxonomic and functional characteristics of macrobenthic communities were tested. Our data and modeling results indicate that bioturbation and bioirrigation alter near-surface pore-water nutrient concentrations towards bottom water values. Besides sediment properties and microbial activity, the biogeochemical fluxes can further be explained by the functional structure of benthic macrofauna. Community bioturbation potential, species richness and biomass of biodiffusers were the best proxies among the tested set of biotic and abiotic parameters and could explain 63% of multivariate total benthic flux variations. The effects of macrobenthos on ecosystem functioning differ between sediment types, specific locations and seasons. Both, species distribution and nutrient fluxes are temporally dynamic. Those natural patterns, as well as potential anthropogenic and natural disturbances (e.g. fishery, storm events), may cause impacts on field data in a way beyond our present capability of quantitative prediction, and require more detailed seasonal studies. The data presented here adds to our understanding of the complexity of natural ecosystem functioning under anthropogenic pressure.